MAKING STEM EXPERIMENT VIDEO FOR SCIENCE LESSON: A SIMPLE FAN - Deby Lovelia Esa; Arief Muttaqiin (UNIVERSITAS NEGERI MEDAN, 2023)
This research aims to produce a valid and practical natural science experiment video of a simple fan on energy in living systems. This video contains elements of STEM and critical thinking skill questions. This research uses the Plomp development model, which consists of three phases, namely the Preliminary research, the prototyping and the assessment. This research was carried out until the Prototyping phase. The research instruments used were validity and practicality questionnaires. The validity tests were conducted to three science education lecturers and the practicality tests were conducted on students at SMPN 15 Padang. The results of the validity test obtained an average Moment Kappa (k) value of 0.85 with the very high category. The results of the practicality test at the one to one evaluation obtained an average Moment Kappa (k) value of 0.92 and at the small group evaluation phase obtained an average Moment Kappa (k) value of 0.93 with the very high category. To find out the students' interest in this experimental video, an interview was conducted as additional data stating which stated that the students were very interested and could help the teacher in deliver on energy material in living systems